Superantigen profiles of emm and emm-like typeable and nontypeable pharyngeal streptococcal isolates of South India - Anand Thangarajan; Rajesh Thangamani; Rajendhran Jeyaprakash; Gunasekaran Paramasamy (BMC, 2012)
Abstract Background The major virulence factors determining the pathogenicity of streptococcal strains include M protein encoded by emm and emm-like (emmL) genes and superantigens. In this study, the distribution of emm, emmL and superantigen genes was analyzed among the streptococcal strains isolated from the patients of acute pharyngitis. Methods The streptococcal strains were isolated from the throat swabs of 1040 patients of acute pharyngitis. The emm and emmL genes were PCR amplified from each strain and sequenced to determine the emm types. The dot-blot hybridization was performed to confirm the pathogens as true emm nontypeable strains. The presence of eleven currently known superantigens was determined in all the strains by multiplex PCR. Results Totally, 124 beta-hemolytic streptococcal strains were isolated and they were classified as group A streptococcus (GAS) [15.3% (19/124)], group C streptococcus (GCS) [59.7% (74/124)] and group G streptococcus (GGS) [25.0% (31/124)]. Among 124 strains, only 35 strains were emm typeable and the remaining 89 strains were emm nontypeable. All GAS isolates were typeable, whereas most of the GCS and GGS strains were nontypeable. These nontypeable strains belong to S. anginosus [75.3% (67/89)] and S. dysgalactiae subsp. equisimilis [24.7% (22/89)]. The emm and emmL types identified in this study include emm12.0 (28.6%), stG643.0 (28.6%), stC46.0 (17.0%), emm30.11 (8.5%), emm3.0 (2.9%), emm48.0 (5.7%), st3343.0 (2.9%), emm107.0 (2.9%) and stS104.2 (2.9%). Various superantigen profiles were observed in typeable as well as nontypeable strains. Conclusions Multiplex PCR analysis revealed the presence of superantigens in all the typeable strains irrespective of their emm types. However, the presence of superantigen genes in emm and emmL nontypeable strains has not been previously reported. In this study, presence of at least one or a combination of superantigen coding genes was identified in all the emm and emmL nontypeable strains. Thus, the superantigens may inevitably play an important role in the pathogenesis of these nontypeable strains in the absence of the primary virulence factor, M protein.